Defining the electroclinical phenotype and outcome of PCDH19‐related epilepsy: A multicenter study. (19th November 2018) - Trivisano, Marina; Pietrafusa, Nicola; Terracciano, Alessandra; Marini, Carla; Mei, Davide; Darra, Francesca; Accorsi, Patrizia; Battaglia, Domenica; Caffi, Lorella; Canevini, Maria P.; Cappelletti, Simona; Cesaroni, Elisabetta; et al.
Summary: Objective: PCDH19‐related epilepsy is an epileptic syndrome with infantile onset, characterized by clustered and fever‐induced seizures, often associated with intellectual disability (ID) and autistic features. The aim of this study was to analyze a large cohort of patients with PCDH19‐related epilepsy and better define the epileptic phenotype, genotype‐phenotype correlations, and related outcome‐predicting factors. Methods: We retrospectively collected genetic, clinical, and electroencephalogram (EEG) data of 61 patients with PCDH19‐related epilepsy followed at 15 epilepsy centers. All consecutively performed EEGs were analyzed, totaling 551. We considered as outcome measures the development of ID, autistic spectrum disorder (ASD), and seizure persistence. The analyzed variables were the following: gender, age at onset, age at study, genetic variant, fever sensitivity, seizure type, cluster occurrence, status epilepticus, EEG abnormalities, and cognitive and behavioral disorders. Receiver operating characteristic curve analysis was performed to evaluate the age at which seizures might decrease in frequency. Results: At last follow‐up (median = 12 years, range = 1.9‐42.1 years), 48 patients (78.7%) had annual seizures/clusters, 13 patients (21.3%) had monthly to weekly seizures, and 12 patients (19.7%) were seizure‐free for ≥2 years. Receiver operating characteristic analysis showed a significant decrease of seizure frequency after the age of 10.5 years (sensitivity = 81.0%, specificity = 70.0%). Thirty‐six patients (59.0%) had ID and behavioral disturbances. ASD was present in 31 patients. An earlier age at epilepsy onset emerged as the only predictive factor for ID ( P = 0.047) and ASD ( P = 0.014). Conversely, age at onset was not a predictive factor for seizure outcome ( P = 0.124). Significance: We found that earlier age at epilepsy onset is related to a significant risk for ID and ASD. Furthermore, long‐term follow‐up showed that after the age of 10 years, seizures decrease in frequency and cognitive and behavioral disturbances remain the primary clinical problems.